Effect of addition of banana stem compost on the growth of jabon (Anthocephalus cadamba Miq.) seedlings growth - Arum Sekar Wulandari; Irdika Mansur; Helga Sugiarti (Jurnal Silvikultur Tropika, 2011)
Addition of compost could increase plant growth. Compost derived from banana stem could be added as admixture in nursery medium for growing jabon seedlings.  This research studied the effect of addition of various composts on the growth of jabon  (Anthocephalus cadamba Miq.) seedlings. The objectives of this study were: (1) to test the quality of compost produced from banana stem in improving the growth of jabon seedlings, and  (2) to learn the effect of composts from banana stem and other composts existing in the market (Ofer, Cocopeat, Guano and  Andam) on the growth of jabon seedlings.